Constructing NiCo2Se4/NiCoS4 heterostructures for high-performance rechargeable aluminum battery cathodes. Issue 16 (28th June 2022) - Zhou, Wei; Du, Yiqun; Kang, Rongkai; Sun, Ximan; Zhang, Wenyang; Wan, Jiaqi; Chen, Guowen; Zhang, Jianxin
Abstract : An aluminum battery based on the NiCo2 Se4 /NiCoS4 cathode delivers a capacity of 112 mA h g −1 after 195 cycles. The charge–discharge principle of the NiCo2 Se4 /NiCoS4 cathode is the Al 3+ intercalation and valence state transition of the Ni, Co, and S elements. Abstract : Rechargeable aluminum batteries (RABs) are regarded as promising candidates for new-generation rechargeable batteries. However, due to the high charge density of Al 3+, the modest cycling performance of RABs is difficult to improve, given the strong coulombic interaction between Al 3+ and host materials. Heterostructure engineering is emerging as a promising strategy to further enhance the electrochemical performance of energy storage devices. Herein, heterostructured NiCo2 Se4 /NiCoS4 prepared via a two-step solvothermal treatment is reported as a new type of RAB cathode material. As expected, the heterostructured NiCo2 Se4 /NiCoS4 cathode delivers a discharged specific capacity of 112 mA h g −1 over 195 cycles. It is instructive to note that the operational mechanism of the RABs is the intercalation of Al 3+ and the redox process of Co, Ni, and S elements.